Peripheral Arterial Thrombosis following Russell's Viper Bites - Senthilkumaran, Subramanian; Patel, Ketan; Rajan, Elanchezhian; Vijayakumar, Pradeep; Miller, Stephen W.; Rucavado, Alexandra; Gilabadi, Soheil; Sonavane, Medha; Richards, Nicholas J.; Williams, Jarred; Williams, Harry F.; Trim, Steven A.; Thirumalaikolundusubramanian, Ponniah; Gutiérrez, José María; Vaiyapuri, Sakthivel (TH Open, 2023)
Envenomings by Russell's viper (Daboia russelii), a species of high medical importance in India and other Asian countries, commonly result in hemorrhage, coagulopathies, necrosis, and acute kidney injury. Although bleeding complications are frequently reported following viper envenomings, thrombotic events occur rarely (reported only in coronary and carotid arteries) with serious consequences. For the first time, we report three serious cases of peripheral arterial thrombosis following Russell's viper bites and their diagnostic, clinical management, and mechanistic insights. These patients developed occlusive thrombi in their peripheral arteries and symptoms despite antivenom treatment. In addition to clinical features, computed tomography angiography was used to diagnose arterial thrombosis and ascertain its precise locations. They were treated using thrombectomy or amputation in one case that presented with gangrenous digits. Mechanistic insights into the pathology through investigations revealed the procoagulant actions of Russell's viper venom in standard clotting tests as well as in rotational thromboelastometry analysis. Notably, Russell's viper venom inhibited agonist-induced platelet activation. The procoagulant effects of Russell's viper venom were inhibited by a matrix metalloprotease inhibitor, marimastat, although a phospholipase A2 inhibitor (varespladib) did not show any inhibitory effects. Russell's viper venom induced pulmonary thrombosis when injected intravenously in mice and thrombi in the microvasculature and affected skeletal muscle when administered locally. These data emphasize the significance of peripheral arterial thrombosis in snakebite victims and provide awareness, mechanisms, and robust strategies for clinicians to tackle this issue in patients.
Keywords: Russell's viper; snakebite envenomation; thrombosis; peripheral arteries; venom